Effects of Moringa Oleifera Mouthwash on Plaque Index in Patients Having Fixed Orthodontic Appliances - Afreen, Rabia; Durrani, Owais Khalid; Bashir, Ulfat; Khan, Fatima; Zulfiqar, Kanwal; Arshad, Nauman (Indus Journal of Bioscience Research, 2025)
Background: With increasing trend towards improved facial esthetics, larger number of people are getting orthodontic treatments. Maintenance of adequate oral hygiene become difficult with fixed orthodontic appliances because tooth brushes can’t reach all the surfaces due to hindrance provided by fixed appliances. Thus, in order to prevent deleterious effects of braces adjunctive oral care measures like flossing and use of an efficient mouthwash is advised by orthodontists. Commercially available chemical mouthwashes especially Chlorhexidine Gluconate is very effective in preventing plaque accumulation, gingivitis and other gum health problems, but it is associated with wide variety of side effects. So, the interest is being shifted to herbal alternatives that are equally effective but have minimal to zero side effects. In the recent history Moringa Oleifera has emerged as a miracle tree and studies have shown that it has numerous health benefits and medicinal advantages as well. It also has anti-inflammatory a property. Objective: The objective of this study was to find out the efficacy of Moringa Oleifera mouthwash in preventing plaque development over the period of five months in patients undergoing orthodontic treatment with fixed appliances. Materials and Method: This parallel arm, triple blinded, randomized controlled trial was done at Islamic International Dental Hospital. Total 60 participants who were starting orthodontic treatment with fixed appliances were included in the study; they were randomly allocated to two groups, Moringa Group and Control group. Plaque Index was recorded before the fixed appliances i.e. T0. One month after that i.e. at T1, PI was recorded again and then a one litter bottle of mouthwash was given to the participants with the detailed instructions on how to use that. Placebo mouthwash was given to control group and Moringa Oleifera mouthwash was given to Moringa group. PI was recorded again after one month i.e. at T2 and then on monthly intervals i.e. T3, T4 and T5. Jamovi and Phyton was used to analyze the results, the difference between PI scores at T0, T1, T2, T3 and T4 was assessed using the Wilcoxon Signed-rank test. P value was set at ≤ 0.05 and was considered significant. Mann Whitney U test was applied to compare the plaque index scores between control and Moringa group. Results: The results showed significant increase in plaque index score in both the groups over time from T0 to T4. But it increases more in the control group as compared to the Moringa group. At T4 there is significant difference in plaque index scores between the two groups, control groups have higher score than the Moringa group. Conclusion: The Moringa Oleifera mouthwash efficiently reduces the plaque accumulation in patients undergoing orthodontic treatment with fixed appliances. Thus, it can be used as an adjunctive oral care measure to prevent gingivitis and other deleterious effects of fixed orthodontic appliances instead of chemical mouthwashes.